Advancing cellular insights: Super-resolution STORM imaging of cytoskeletal structures in human stem and cancer cells - Anupam Bharadwaj; Amalesh Kumar; Sam Padalumavunkal Mathew; Rumela Mitra; Jina Bhattacharyya; Bithiah Grace Jaganathan; Bosanta R. Boruah (Biochemistry and Biophysics Reports, 2024)
Fluorescence microscopy is an important tool for cell biology and cancer research. Present-day approach of implementing advanced optical microscopy methods combined with immunofluorescence labelling of specific proteins in cells is now able to deliver optical super-resolution up to ∼25 nm. Here we perform super-resolved imaging using standard immunostaining protocol combined with easy stochastic optical reconstruction microscopy (easySTORM) to observe structural differences of two cytoskeleton elements, actin and tubulin in three different cell types namely human bone marrow-derived mesenchymal stem cells (MSCs), human glioblastoma (U87MG) and breast cancer (MDAMB-231) cells. The average width of the actin bundle obtained from STORM images of stem cells is observed to be larger than the same for U87MG and MDAMB-231 cells. No significant difference is however noticed in the width of the tubulin within the same cells. We also study the functional effect on the 2D migration potential of MDAMB-231 cells silenced for NICD1 and β-catenin. Although similar migration speed is observed for cells with the above two conditions compared to their control cells, easySTORM images show that widths of the actin in MDAMB-231 cells in β-catenin silenced is significantly lower than the same in control cells. Such minute differences however are not observable in widefield images. The outcome of our easySTORM investigation should benefit the researchers carrying out detailed investigations of the cellular structure and potential therapeutic applications.